Sites of competition in the selective hepatic uptake of rifamycin-SV, flavaspidic acid, bilirubin, and bromsulphthalein. Issue 3 (March 1974) - Kenwright, S.; Levi, A. J.
Abstract : In rats both rifamycin-SV and flavaspidic acid impaired the disappearance of bromsulphthalein (BSP) from plasma. The addition of rifamycin-SV to rat liver supernatant containing BSP did not displace BSP from ligandin or Z protein unless it was added in very high concentration. In similar studies in vitro with flavaspidic acid, BSP was displaced from Z protein even at low concentrations of flavaspidic acid, whereas there was only a minor effect on the binding to ligandin. The intravenous administration of rifamycin to Gunn rats raised the plasma bilirubin concentration slightly after 30 minutes whereas flavaspidic acid was without significant effect. At 30 minutes the amount of bilirubin in the liver was markedly reduced by rifamycin and moderately depressed by flavaspidic acid. Although both the rifamycin and flavaspidic acid lowered the bilirubin in cell sap, the main effect of flavaspidic acid appeared to be on binding to Z protein. Rifamycin reduced the amount bound to both ligandin and Z protein. It is suggested that flavaspidic acid acted on the hepatic uptake of bilirubin and BSP predominantly by competing for binding to Z protein. Rifamycin-SV acted at a different site, probably blocking uptake at the plasma membrane.